Effect of social support on Muslim women’s sporting activities: mediating effect of psychological adjustment - Chen, Nan; Qiao, Fengjie (Frontiers in Psychology, 2024)
Objective: This study explores the relationship between social support and sporting activities of Muslim women and constructs a mediation model through role of psychological adjustment.Methods: Using stratified cluster sampling, 301 Muslim women were measured in group psychology using the Social Support Scale and the Sports Activities and Psychological Adjustment Scale. The statistical software SPSS 24.0 and SPSS PROCESS 3.3 were used for statistical processing. The common-method variation test was carried out using the Harman single-factor control test. Finally, the Bootstrap sampling test method and process plug-in were used to test the significance of the intermediary effect.Results: (1) Social support has a significant predictive effect on sports activities (β = 0.32, P < 0.001); (2) psychological adjustment (β = 0.552, P < 0.001) mediates the relationship between social support and sporting activities (social support → psychological adjustment → sporting activities (95% Cl: 0.093, 0.323)).Conclusions: Social support positively influences sporting participation among Muslim women, and psychological adjustment mediates this relationship. Strengthening social support for Muslim women can enhance their psychological adjustment, thereby improving their participation in sporting activities and offering valuable theoretical and practical guidance.